2016
DOI: 10.1016/j.biopsych.2015.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Heterogeneity in Clinical Cohorts Using Normative Models: Beyond Case-Control Studies

Abstract: BackgroundDespite many successes, the case-control approach is problematic in biomedical science. It introduces an artificial symmetry whereby all clinical groups (e.g., patients and control subjects) are assumed to be well defined, when biologically they are often highly heterogeneous. By definition, it also precludes inference over the validity of the diagnostic labels. In response, the National Institute of Mental Health Research Domain Criteria proposes to map relationships between symptom dimensions and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
489
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 449 publications
(555 citation statements)
references
References 42 publications
(50 reference statements)
6
489
0
1
Order By: Relevance
“…Using case-control comparisons and searching for common alterations exhibited across the group can easily obscure nonshared, heterogeneous patterns of differences across individuals. In other words, it is possible that certain types of statistics, which largely rest on the assumption of group-level similarity, are inappropriate and may mask important differences that can be better resolved by applying individually-sensitive analytic approaches (Byrge et al, 2015;Dubois & Adolphs, 2016;Marquand et al, 2019;Marquand, Rezek, Buitelaar, & Beckmann, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Using case-control comparisons and searching for common alterations exhibited across the group can easily obscure nonshared, heterogeneous patterns of differences across individuals. In other words, it is possible that certain types of statistics, which largely rest on the assumption of group-level similarity, are inappropriate and may mask important differences that can be better resolved by applying individually-sensitive analytic approaches (Byrge et al, 2015;Dubois & Adolphs, 2016;Marquand et al, 2019;Marquand, Rezek, Buitelaar, & Beckmann, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, the robustness and generalizability of such studies have been brought into question (Dinga et al, ), which may be partly due to substantial brain heterogeneity within groups, which has been illustrated in terms of morphometry in schizophrenia (Alnæs et al, ). Alternatively, dimensional measures such as brain age prediction (Kaufmann et al, In press) and normative modeling (Marquand et al, ; Marquand, Rezek, Buitelaar, & Beckmann, ) have shown promising results in elucidating brain heterogeneity in mental disorders such as schizophrenia (Wolfers et al, ) and attention deficit/hyperactivity disorder (Wolfers et al, ). An important consideration is the multicausal nature of depression, which means that it is likely that including other measures such as psychosocial, cognitive, and genetic factors would increase the explained variance, beyond brain imaging by itself.…”
Section: Discussionmentioning
confidence: 99%
“…The alternative is to not merely focus on where groups differ, but to model where individuals differ. The illustration that many of the tools we use for measuring aspects of biology provide little or no diagnostic specificity and the evidence of commonalities across diagnostic categories reinforces the value of considering the individual instead of the group . Furthermore, given the similarities between brain diseases and ageing I described earlier, then it is even more important to consider the individual in the context of what would be expected given their age.…”
Section: Focusing On Commonalities Could Lead To a Paradigm Shiftmentioning
confidence: 95%